Influence of industrial effluents on quality and fertility of guinea savanna alfisols at NOUN research farm, Kaduna, Nigeria (Agriculture, Food, and Natural Resources Journal, 2026)
Industrial wastewater is an increasing environmental concern in agricultural areas because of its effects on soil properties, nutrient dynamics, and long-term productivity. This study assessed the influence of industrial effluents on the chemical quality and fertility status of Guinea Savanna Alfisols at the NOUN Research Farm, Rigachikun, Kaduna State, Nigeria. A comparative sampling approach was used involving effluent-impacted and control plots, with soil collected at 0–15 cm and 15–30 cm depths. Laboratory analyses determined soil pH, electrical conductivity (EC), organic carbon (OC), total nitrogen (TN), available phosphorus (P), exchangeable bases (Ca, Mg, K, and Na), cation exchange capacity (CEC), and selected heavy metals (Zn, Cu, Pb, and Cd). Soil pH ranged from 6.72–7.05, indicating slightly acidic to neutral conditions. Electrical conductivity was higher in effluent-affected soils (0.72–0.96 dS m⁻¹) than in control soils (0.28–0.31 dS m⁻¹). Organic carbon ranged from 0.621.15%, while total nitrogen varied between 0.06–0.11%. Available phosphorus (7.8–15.4 mg kg⁻¹) was generally higher in effluent-impacted plots. Exchangeable sodium increased from 0.24–0.28 cmol kg⁻¹ in control soils to 0.51–0.62 cmol kg⁻¹ in affected soils, while CEC ranged from 6.5–9.8 cmol kg⁻¹. Heavy metal concentrations were also higher in impacted soils: Zn (1.202.84 mg kg⁻¹), Cu (0.70–1.36 mg kg⁻¹), Pb (15.7–42.5 mg kg⁻¹), and Cd (0.893.18 mg kg⁻¹), with Cd slightly above recommended limits in surface soils. Industrial effluents may improve nutrient availability in the short term but increase salinity and heavy metal accumulation, threatening long-term soil health and crop safety. Effluent treatment, regular soil monitoring, and appropriate fertility management are therefore recommended.